Comparison of Cost-Effectiveness, Safety, and Efficacy of Rosuvastatin Versus Atorvastatin, Pravastatin, and Simvastatin in Dyslipidemic Diabetic Patients With or Without Metabolic Syndrome - Bener, Abdulbari; Dogan, Muzeyyen; Barakat, Lolwa; Al-Hamaq, Abdulla O. A. A. (SAGE PUBLICATIONS INC, 2014)
Aim: The aim of the current study was to determine the efficacy of the 4 most commonly prescribed statins (rosuvastatin, atorvastatin, pravastatin, and simvastatin) for managing dyslipidemia among diabetic patients with and without metabolic syndrome (MetS). Material and Methods: This was a cohort observational population-based study conducted at Hamad Medical Hospital and Primary Health Care Centre. The participants were 1542 consecutive diabetes patients who were diagnosed with dyslipidemia and were prescribed any of the indicated statins. Sociodemographic and clinical characteristics were taken from medical records, and lipid profile at baseline and 2 years after the initiation of statin therapy were retrieved from electronic medical records database (EMR-viewer). Reduction in different lipid profile after 2 years of therapy was compared among different types of statins between patients with and without MetS. Results: Out of total 1542 subjects, 562(36.4%) were diagnosed with MetS using the criteria of International Diabetes Federation. Among those with MetS, 125 were prescribed with atorvastatin, 162 pravastatin, 177 rosuvastatin, and 98 simvastatin. Among those without MetS, 365 used atorvastatin, 172 pravastatin, 345 rosuvastatin, and 98 simvastatin therapies. Among patients with MetS, rosuvastatin therapy resulted in significantly higher low-density lipoprotein cholesterol and total cholesterol reduction (23%, P = .006; and 20.3%, P = .015, respectively) as compared with other statins. Similarly, significantly higher percentage of patients receiving rosuvastatin therapy were successful in achieving the target of total cholesterol < 4 mmol/L and triglycerides < 1.7 mmol/L after 2 years (38.4%, P = .012; and 67.2%, P = .010, respectively) as compared with other therapies. In contrast, among patients without MetS, rosuvastatin therapy resulted in highest percentage drop in total cholesterol (20.1%; P = .016) than other statin therapies. Conclusion: The present study confirmed that rosuvastatin therapy in commonly prescribed doses is the most effective statin for low-density lipoprotein cholesterol goal achievement and for improving the lipid profile in hypercholesterolemic diabetic patients with and without MetS.
Keywords: efficacy; rosuvastatin; atorvastatin; simvastatin; pravastatin; dyslipidemic diabetic patients; CARDIOVASCULAR-DISEASE; CHOLESTEROL GOALS; LIPID GOALS; HIGH-RISK; POPULATION; PREVALENCE; ACHIEVEMENT; MELLITUS; STATIN; LDL; General & Internal Medicine